Pengembangan Model Bisnis Berkelanjutan Untuk UMKM Kerupuk Udang Dan Payus Di Era Digital - Faridah Nur Azizah; Maharani Ikaningtyas (Jurnal Pelayanan Hubungan Masyarakat, 2023)
This research discusses the development of sustainable business models for MSMEs, Shrimp Crackers & Payus Mak Sah in the digital era. Qualitative methods are used with in-depth interviews and content analysis. The findings show that digital marketing strategies through Instagram (IG) and product catalogs have a positive impact on the development of this MSME business. Internal factors, such as knowledge and skills in digital marketing, as well as environmental support, play an important role in the development of this business. In addition, this research reveals the positive social influence of developing this sustainable business model in increasing the income and welfare of business owners, as well as expanding public awareness of local products. This research provides valuable insights for similar MSMEs in developing sustainable business models in the digital era.)